Elite female athletes` experiences and perceptions of the menstrual cycle on training and sport performance - Brown, N.; Knight, C. J.; Forrest (née Whyte), L. J. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The purpose of the current study was two-fold; 1) to examine elite female athletes` experiences of their menstrual cycle, with a focus upon the impact on training and competition performance, and 2) the openness of conversation pertaining to the menstrual cycle with coaching and support staff. Following receipt of institutional ethical approval, individual semi-structured interviews were conducted with 17 elite female athletes (25.5 ± 4.7yrs) from multiple sports. Results revealed athletes` experiencing a natural menstrual cycle reported physical symptoms alongside mood disturbances and reduced motivation to train. The decision to actively control the menstrual cycle was often triggered by a desire to reduce the effect on competition, to lessen anxieties about making required weight or reduce distraction to manage during competition. Athletes indicated an openness to talk about the menstrual cycle to other females, however, there was variation in the comfort athletes experienced regarding talking to male coaches.